2014
DOI: 10.1080/13803395.2014.892916
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve moderates relation between global cognition and functional status in older adults

Abstract: The ability to perform instrumental activities of daily living (IADLs) is necessary for independent living. Research suggests that community-dwelling older adults are at risk for experiencing subtle decrements in the performance of IADLs. Neuropsychological tests have been used to account for differences in IADL status. Studies of the relationship between cognitive ability and functional status have produced variable results, however, and cognitive ability appears to be only a moderate predictor. Several studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Female sex may play a role in poststroke cognitive impairment by related degenerative pathology, which would interact with vascular pathology as well [ 35 ], and unsurprisingly, greater prestroke cognitive decline was observed in VCI patients in our study. The beneficial effect of education could be that a higher education level indicated better cognitive reserve, in this way, patients with higher reserve would show an altered, compensatory network to maintain function in the face of age-related pathophysiological changes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Female sex may play a role in poststroke cognitive impairment by related degenerative pathology, which would interact with vascular pathology as well [ 35 ], and unsurprisingly, greater prestroke cognitive decline was observed in VCI patients in our study. The beneficial effect of education could be that a higher education level indicated better cognitive reserve, in this way, patients with higher reserve would show an altered, compensatory network to maintain function in the face of age-related pathophysiological changes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research does suggest, however, that global cognition assessed by such measures as the MMSE as well as measures of executive functioning such as the Delis–Kaplan Executive Function System (Delis et al ., 2004; Homack et al ., 2005), account for the greatest proportion of variance of functional ability (Duda et al ., 2014). Several studies have shown specific associations between executive functions (Mariani et al ., 2008; Pereira et al ., 2010), memory and psychomotor speed (Barberger-Gateau et al ., 1993; Tuokko et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…While clinicians frequently use neuropsychological measures to account for differences in functional status among older adults these tests are designed to evaluate specific cognitive abilities rather than functional abilities, and there is little evidence to support such test use in this manner (Chaytor and Schmitter-Edgecombe, 2003; Farias et al ., 2003). Research does suggest, however, that global cognition assessed by such measures as the MMSE as well as measures of executive functioning such as the Delis–Kaplan Executive Function System (Delis et al ., 2004; Homack et al ., 2005), account for the greatest proportion of variance of functional ability (Duda et al ., 2014). Several studies have shown specific associations between executive functions (Mariani et al ., 2008; Pereira et al ., 2010), memory and psychomotor speed (Barberger-Gateau et al ., 1993; Tuokko et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The CAC composite score served as the dependent variable in one regression model, and the SEC composite score served as the dependent variable in a second model. Consideration of covariates was guided by literature which indicated that demographics (gender, age, race, and education), emotional status (self-reported depression), cortical thickness, and cognition are related (Austin, Mitchell, & Goodwin, 2001; Daniel et al, 2013; Duda, Puente, & Miller, 2014; Gallo, Rebok, Tennstedt, Wadley, & Horgas, 2003; Kim et al, 2012; Rexroth et al, 2013). Self-reported depression (CES-D total score) was excluded based on its highly positive skew (Skewness = 1.146) and the observation that no participant reported a clinically significant level of depression (defined as a score > 16; See Table 2).…”
Section: Methodsmentioning
confidence: 99%